Long‐term dynamics of Alpine ungulates suggest interspecific competition. (20th July 2019) - Corlatti, L.; Bonardi, A.; Bragalanti, N.; Pedrotti, L.
Abstract: Studies identifying interspecific competition require the investigation of negative long‐term effects between sympatric species showing overlap in resource use. A potential for competition exists between red deer Cervus elaphus and chamois Rupicapra spp., as revealed by the high dietary overlap observed throughout the range where the species co‐occur. Furthermore, some studies have recently reported negative demographic consequences on chamois populations living in sympatry with red deer. Using time series of counts spanning 35 years between 1984 and 2018 in the Stelvio National Park (Central Italian Alps), we tested for density dependence using state‐space models and explored the evidence of competitive interaction through Ricker‐like models on the growth rate of both species. We contrasted alternative hypotheses for the processes explaining the trends of (decreasing) chamois and (increasing) red deer populations. We expected chamois dynamics to be negatively affected by increasing deer abundance, while deer dynamics should be primarily affected by climate forcing and density dependence. We found evidence that resources were limiting for both species. In particular, growth rates were negatively affected by the synergistic effect of winter weather conditions and density dependence. The most important variable limiting the chamois population, however, was the increase in red deer numbers. The dynamics of this species was unaffected by chamois numbers. While causality cannot be inferred from the data, these results are consistent with the hypothesis of a negative effect of red deer on chamois dynamics, thus supporting the occurrence of interference or exploitation competition between sympatric mountain‐dwelling ungulates. Understanding the processes underlying temporal dynamics is pivotal for informed management of wildlife. Consequences of interspecific competition should be carefully evaluated where the populations of the weaker competitor are of conservation concern, especially in the light of the negative effects of anthropogenic environmental change on animal populations. Abstract : We used long‐term count series to contrast alternative process hypotheses to explain the couple dynamics of chamois and red deer in the Italian Alps. We found evidence that the most important variable limiting the chamois population was the numeric increase in red deer, whose dynamics was independent of chamois. These results are consistent with the hypothesis of a negative effect of red deer on chamois demography.